Disinvestment - A Financial Analysis of Selected Metal Companies. - Bansal, Monica (Gyan Management Journal, 2011)
There are several reasons for disinvestment of the public sector units and mainly among these is inefficient working. Most of the enterprises of the public sector were running into loss. The main reason behind it was that the managers of public sector enterprises were not free to take any decision independently. All important decisions were taken by the ministers, who were more concerned with their political interests. It took long time to take decision. Consequently, production capacity remained under utilized, managers failed to function in a responsible manner causing productivity to go down. All these factors contributed to the inefficiency of the public sector which a result of disinvestment. The main objective of this research paper is to know about the financial position of the selected metal companies on the basis of solvency position. It is concluded that India has a substantial middle class; a huge market; relatively well-established capital markets; flexible and enterprising financial system; and rich human resources, particularly business, technical and engineering skills. These factors make the circumstances in India favourable for the success of a disinvestment program. The private sector in India is dynamic and ready to play a leading role in the nation’s development.